Education and Promotion of Online Transaction Services for Traditional Market Traders in Sleman: An Alternative to Alleviate the Impact of COVID-19 "Layanan Online Pasar Ing Sleman (LOPIS)" - Mukhlis Mukhlis; Nabella Duta Nusa; Rezki Wulan Ramadhanty (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Spreading in Special Region of Yogyakarta (DIY) since March 2020, the COVID-19 pandemic has slowed down economic activities. Activities in traditional markets decreased due to restricted operating time and people movement. Traders should use online transactions to reach potential consumers. Expanding market segments is also necessary to target the younger generation who regularly use online transactions. Unluckily, traders were not well-trained in online transactions. This activity was aimed to encourage well-implemented online transaction services by traditional market traders in Sleman Regency. Four measures were taken: 1) identifying conditions of traders, 2) formulating online transaction models for traders and potential consumers, 3) online transaction training, and 4) Disseminating/promoting online transaction services. A survey was done in 22 of 37 markets to identify market conditions. Collected data were analysed using the interactive model. Formulated online transaction model includes offer, order, payment and delivery of products. Traders in 25 markets received the training. Service marketing activities include publications on social media, data presentation of markets and traders on Google Maps page, and webinar. All activities were conducted under the tagline "LOPIS (Layanan Online Pasar Ing Sleman)", which means Online Services by Traditional Markets in Sleman Regency. Monitoring is planned for three months after the training is conducted. However, this monitoring could not be carried out due to a significant increase in COVID-19 cases, hence the limitation of this community service activity.